Analysis of Prestressed Visco-Elastic Structures by the Virtual Distortion Method - Holnicki-Szulc, J. (Engineering Transactions, 1992)
New method of modeling of visco-plastic structures is presented. A fictitious virtual (initial) distortions (controlled in time in a prescribed way) introduced to elastic structure can cause the same resultant strains and stresses as in a visco-elastic structure without virtual distortions but under the same loading. The presented method can describe structures with nonhomogeneously distributed mechanical properties. It allows also to take into account the states of prestressing. Therefore, it can be a helpful tool to solve problems of optimal prestress for visco-elastic structures.